2021
DOI: 10.3390/w13162169
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Coastal Vulnerability to the Ongoing Sea Level Rise for the Exquisite Rhodes Island (SE Aegean Sea, Greece)

Abstract: The foreseeable acceleration of global sea level rise could potentially pose a major threat to the natural charm and functional integrity of the world-renowned tourist coastal attractions of Rhodes Island, as a result of the anticipated increasing frequency of flooding and erosion events. Hence, this study aims to determine the most vulnerable segments (in terms of physical impact) of the Rhodes coastline through the widely accepted coastal vulnerability index (CVI), applying a combination of well-known, broad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 108 publications
1
22
0
Order By: Relevance
“…The database was processed through a GIS environment, using the ArcMap (v. 10.8) and ArcGIS Pro (v. 2.8). The ranking scheme for the evaluation of the parameters used was created after combining different approaches of widely used indices (e.g., [15][16][17], with later modifications (e.g., [21,24,33,50,88]), as well as more complex indices (e.g., [25][26][27]51]). The ranking refers to factors that affect the exposure (e.g., Mean-Max significant wave height), sensitivity (e.g., coastal landforms), and adaptive capacity (e.g., distance from hospitals, fire departments, police stations), which are crucial components of resilience in the coastal area.…”
Section: Methodsmentioning
confidence: 99%
“…The database was processed through a GIS environment, using the ArcMap (v. 10.8) and ArcGIS Pro (v. 2.8). The ranking scheme for the evaluation of the parameters used was created after combining different approaches of widely used indices (e.g., [15][16][17], with later modifications (e.g., [21,24,33,50,88]), as well as more complex indices (e.g., [25][26][27]51]). The ranking refers to factors that affect the exposure (e.g., Mean-Max significant wave height), sensitivity (e.g., coastal landforms), and adaptive capacity (e.g., distance from hospitals, fire departments, police stations), which are crucial components of resilience in the coastal area.…”
Section: Methodsmentioning
confidence: 99%
“…Vulnerability is a dynamic concept that changes through time and across societies [26]. While coastal vulnerability assessment has evolved into a mature science with numerous publications attempting to modify or update baseline studies (e.g., [27]), depending on the research scope of each authors' team (e.g., geological aspects) [28,29], port vulnerability assessment is still quite a challenging issue, considering the complexity of this infrastructure system. Based on the current literature review, variations were observed in the methodologies applied to quantify vulnerability, the aspects examined to approach vulnerability issues (e.g., ecological, socioeconomic, and physical aspects), and the number and category of parameters integrated into assessment applications, as further explained below.…”
Section: Current Port Vulnerability Frameworkmentioning
confidence: 99%
“…The salient can be maintained for a period of a few months to a few years, switching afterwards to a tombolo again as a result of coastal morphodynamics. This changeable landform seems to adapt its shape to the dominant wave regime, since the tidal range is very low (a few tens of centimeters) [26]. It is quite possible that during the constructive periods, sediment being transported from the nearshore zone to the beach nourishes and feeds the tombolo, while during the destructive periods, sediment moves in the opposite direction to the sea building or expands submerged longitudinal sandbar.…”
Section: The Study Areamentioning
confidence: 99%
“…Particularly, Prasonisi and the broader area is integrated at the Natura_2000 network as a Special Protection Area (SPA), Site of Community Importance (SCI), and Special Area of Conservation (SAC) with the code GR4210031 and site name "Notio Akro Rodou, Prasonisi, Ygrotopos Livadi Kattavias" since 2005. It is also well known for different tourist activities such as windsurfing, kitesurfing, hotel amenities, beach bars, etc., due to its distinctive morphology and since it is exposed to a variety of wind-wave conditions [26]. The mean seafloor slope at the northwestern side of the tombolo is 1%, which is about half of that at the southeastern side (2%).…”
Section: The Study Areamentioning
confidence: 99%